2021
DOI: 10.18502/ijrm.v19i8.9621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrauterine granulocyte-colony stimulating factor administration on in vitro fertilization outcome in women with moderate-to-severe endometriosis: An RCT

Abstract: Background: Nearly 25-50% of infertile women have endometriosis. There are reports of disorders in the expression of granulocyte colony-stimulating factor (G-CSF) receptors in women with endometriosis. Objective: To examine the effect of intrauterine administration of G-CSF in in vitro fertilization (IVF) cycles on the fertility rate of infertile women with moderate-to-severe endometriosis. Materials and Methods: This clinical trial was conducted on 66 infertile women with moderate-to-severe endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…With regards to other medical therapies prior to MAR, Kashani et al found that in women with moderate-to-severe endometriosis, granulocyte-colony stimulating factor prior to IVF/ICSI does not improve the CPR [38]. The RCT of Guo et al found no difference in the clinical or ongoing pregnancy rate for women with advanced endometriosis treated with medroxyprogesterone acetate, dydrogesterone or progesterone prior to IVF [39].…”
Section: Medical Therapies As An Adjunct To Medically Assisted Reprod...mentioning
confidence: 99%
“…With regards to other medical therapies prior to MAR, Kashani et al found that in women with moderate-to-severe endometriosis, granulocyte-colony stimulating factor prior to IVF/ICSI does not improve the CPR [38]. The RCT of Guo et al found no difference in the clinical or ongoing pregnancy rate for women with advanced endometriosis treated with medroxyprogesterone acetate, dydrogesterone or progesterone prior to IVF [39].…”
Section: Medical Therapies As An Adjunct To Medically Assisted Reprod...mentioning
confidence: 99%